Samii's Essentials in Neurosurgery - Ramina, Ricardo; de Aguiar, Paulo Henrique Pires; Tatagiba, Marcos (Springer Berlin Heidelberg : Imprint: Springer, 2014)
This second edition of Samii's Essentials in Neurosurgery contains revised and updated versions of chapters from the first edition plus contributions on new topics written by leading neurosurgeons who were trained by Professor Madjid Samii in Hannover, Germany.  Almost all fields of neurosurgery are covered. The authors follow the traditional principles of Samii's philosophy in the diagnosis and management of various neurosurgical pathologies, while presenting their own personal experiences. The extensively illustrated texts document clearly how cutting-edge technology in neurosurgery is being applied in new approaches and techniques. This book will greatly assist neurosurgeons, ENT surgeons, neuroradiologists, neurologists, and neurophysiotherapists in their everyday practice.